Prediktor Non-Kognitif Kegigihan Tugas Mahasiswa: Studi Kasus Pada Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Ampel Surabaya - Mukhoiyaroh Mukhoiyaroh (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2019)
This study aims to reveal non cognitive predictors of student task persistence. This study used confirmatory factor analysis to demonstrate predictor factors of the Students task persistence based on theory. The instrument of this study was a perception questionnaire on 210 students of the Tarbiyah and Teacher Training Faculties of UIN Sunan Ampel Surabaya. Factors tested from confirmatory factor analysis were learning motivation, self-efficacy, time on task and effort of task. The results showed that the non cognitive predictors of student task persistence based on the magnitude of successive influences were learning motivation, then time on task, self-efficacy and effort of task